Body image in recently diagnosed young women with early breast cancer. Issue 8 (7th November 2012) - Rosenberg, Shoshana M.; Tamimi, Rulla M.; Gelber, Shari; Ruddy, Kathryn J.; Kereakoglow, Sandra; Borges, Virginia F.; Come, Steven E.; Schapira, Lidia; Winer, Eric P.; Partridge, Ann H.
Abstract: Objective: To assess body image concerns among young women following a breast cancer diagnosis. Methods: A total of 419 women with recently diagnosed stage 0–III breast cancer were surveyed following enrollment as part of a prospective cohort study of women age 40 or younger at diagnosis. Body image was assessed using three items from the psycho‐social scale of the Cancer Rehabilitation Evaluation System (CARES). CARES scores range from 0 to 4, with higher scores indicative of greater image concerns. Mean CARES scores were calculated and compared between treatment groups using t‐tests and analysis of variance. Multiple linear regression models were fit to evaluate the relationship between physical and psychological factors and body image. Results: Mean time from diagnosis to completion of the baseline survey was 5.2 months. The mean CARES score for all women was 1.28. Mean CARES scores in the mastectomy‐only group (1.87) and in the mastectomy with reconstruction group (1.52) were significantly higher ( p  < 0.0001) compared with the scores in the lumpectomy group (0.85), indicating that radical surgery was associated with more body image concerns. Radiation ( p  = 0.01), anxiety ( p  = 0.0001), depression ( p  < 0.0001), fatigue ( p  = 0.04), musculoskeletal pain symptoms ( p  < 0.0001), weight gain ( p  = 0.01), and weight loss ( p  = 0.02), in addition to surgery type ( p  < 0.0001), were all associated with more body image concerns in the multi‐variable analysis. Conclusion: This analysis highlights the impact of treatment, along with physical and psychological factors, on body image early in the survivorship period. Our findings provide targets for potential future intervention and may aid young women in the surgical decision‐making process. Copyright © 2012 John Wiley & Sons, Ltd.